EFFECT OF SAILKITE IN IMPROVING TRAWL GEAR PERFORMANCE - BOOPENDRANATH, M R; PILLAI, N SUBRAMONIA; KUNJIPALU, K K; RAO, K KRISHNA (Fishery Technology, 2017)
Effectiveness of sailkite has been evaluated in two trawl designs, namely, a 25 m high opening trawl and a 32 m large mesh demersal trawl, rigged with sailkite through full scale comparative field trials. A 25 m high opening trawl showed significant increase in total catch by 54.4% ribbon fish (Trichiurus spp.) alone by 138.3% with a reductionin miscellaneous catch, comprising mostly small sciaenids and juvenile fish, by 13.2% while 32 m large mesh demersal trawl showed an improvement in total catch by 9% , ribbon fish by 17.2% and miscellaneous catch by 7.7%. The difference in fishing performance between the two gear arrangements has been attributed to changed net mouth configuration because of higher head line lift and also thepossible herding effect on the fish in the vicinity of trawl mouth, due to addition of sailkite.